What information is contained in experimentally determined lipid profiles? - Schwudke, Dominik (Frontiers in Analytical Science, 2023)
It is long known that hundreds of molecular species make up the cellular lipidome. In this minireview, I will discuss what considerations have to be taken for interpreting membrane and storage lipid profile changes that are often the focal point of lipidomics studies. Further insights will be given how most conserved molecular pattern are formed in eukaryotic systems and what are the consequences for perturbation of lipid homeostasis. I will emphasis the implications of lipid identification specificity and experimental variability on modelling membrane structure and systemic responses. Profile changes of membrane and storage lipids are bound to the kinetics of the metabolic system and experimental design and functional interpretation in lipidomics research should be adapted accordingly.